Geochemistry of Cryoconite Holes, Troll Blue Ice Area, Antarctica - Hodson, Andrew (Zenodo, 2022)
Introduction Cryoconite holes, snow and glacier ice were sampled in eight localities of blue ice in the vicinity of Troll Station, Antarctica during December 2019 and January 2020. The samples were collected as part of the Research Council of Norway-funded BIOICE Project (Grant No. 288402) by Prof. Andy Hodson and Dr Aga Nowak. Data are available as a single Excel spreadsheet with two tabs: one containing the chemistry data and the other containing the location and dimension of the holes, where available. Contact : Andrew.Hodson@unis.no Methods Cryoconite holes in the Troll blue ice area are typically covered by an ice lid, even during summer, when subsurface melting is caused by light penetration through the ice and its absorption by underlying debris particles. Access to the underlying water was therefore achieved first by drilling through the ice lid with a 5 cm Kovacs ice auger. The auger was cleaned at each site before use and the ice chips from the lid were sampled, taking care to ensure a depth-integrated sample was collected in each case. Once the lid was penetrated, a syringe was used to extract water from the hole beneath the lid. Samples of glacier ice were taken by drilling the ice auger into the glacier beside the holes. Samples for major ion analysis (here Ca 2+ , Mg 2+ , Na + , K + , Cl - , SO 4 2- ) were syringe-filtered through 0.45 µm Whatman Puradisc Aqua 30 filters and stored in 50 mL Corning centrifuge tubes after being rinsed with filtrate. The analysis was conducted on Dionex DX90 Ion Chromatographs (University of Sheffield, UK) calibrated in the range 0.01-2 mg L -1 for cations and in the range 0.25-2 mg L -1 for anions. Precision errors for these ions were all <2% for mid-range standards, while the detection limit was ≤ 0.01 mg L -1 for cations and 0.05 mg L -1 for anions (calculated as three times the standard deviation of ten blanks). All ions described above are reported in mg L -1 . Quantification of NH 4 + , PO 4 3- , NO 3 - and Si in the above samples was conducted using a ...